2019
DOI: 10.1039/c8ay02779j
|View full text |Cite
|
Sign up to set email alerts
|

Papain-stabilized silver nanoclusters: dual emission and ratiometric fluorescent sensing of ferrous ions

Abstract: Herein, a dual emissive fluorescent probe for Fe2+ based on papain-stabilized Ag nanoclusters was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…Many methodologies have been developed for preparing AgNCs, which rely on the use of different organic or biological templates, such as proteins, peptides, and polyelectrolytes [25,26] . Remarkably, the use of scaffolds helps to prevent particle aggregation during nanocluster synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many methodologies have been developed for preparing AgNCs, which rely on the use of different organic or biological templates, such as proteins, peptides, and polyelectrolytes [25,26] . Remarkably, the use of scaffolds helps to prevent particle aggregation during nanocluster synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Many methodologies have been developed for preparing AgNCs, which rely on the use of different organic or biological templates, such as proteins, peptides, and polyelectrolytes. [25,26] Remarkably, the use of scaffolds helps to prevent particle aggregation during nanocluster synthesis. Notably, most of these studies have reported the use of AgNCs as fluorescent probes for the detection of a wide range of analytes, such as metal ions [27] and organic compounds [28,29] with approaches relying on measuring fluorescence quenching.…”
Section: Introductionmentioning
confidence: 99%
“…另一种 是只由一种组分构成的探针(图 2), 该探针中的识别单 元和荧光发色基团是同一结构单元, 该类探针的合成过 程相对简单 [25][26] . 对于 Fe 2+ 的检测, 一方面由于 Fe 2+ 和 Fe 3+ 不同的氧 化态彼此互变, 导致很难建立高特异性的探针; 另一方 面, 由于顺磁性的 Fe 2+ 和荧光团之间强的作用力通常会 诱导荧光猝灭, 造成所构建的探针一部分是"on-off"型 的, 这类探针受生物自发荧光的影响, 不便于观察 [27][28][29] . 基于"off-on"型的 Fe 2+ 响应探针数量也很少, 而且大多 数只被应用到细胞中 Fe 2+ 的检测, 而构建能够特异性检 测动物模型中某一器官 Fe 2+ 的浓度变化情况的探针, 还 有待于深入发掘研究 [30][31][32] .…”
unclassified